Linkage between Social Movements, Active Citizenship and Democratic Innovation: an Overview for a new Research Agenda - Nenad Markovikj, Zoran Ilievski and Ivan Damjanovski (My University, 2019)
The paper engages in examining the connection between social movements, active citizenship and democratic innovation. Although there is an obvious commonality between the subjects, its neglect in the academic literature comes as a big surprise. In this sense, the paper aims at instigating a discussion on the linkages between social movements, active citizenship and democratic innovation by raising a number of questions which could be directional for future research endeavors. Primarily, the paper defines the terms social movements and active citizenship in order to establish the categorial apparatus it operates with. The following part of the paper briefly analyzes social movements as democratizing agents as well as the reasons for reemergence of social movements in Southeast Europe. In the last part the paper analyzes the concept of democratic innovation, its definition, theoretical and methodological approaches as well as empirical findings in the area.